Stylistic Features of Causative Verbs in the Uzbek Language - Karimjonova Shahlo Ravshanjonovna (PT FORMOSA CENDEKIA GLOBAL, 2023)
The category of causation (Latin causa - cause) is related to the philosophical concepts of cause and effect. Causality is one of the main forms of interdependence and interdependence of the processes and phenomena of objective reality. It is known that causality has a universal meaning and exists in all forms of matter movement. Cause and effect reflect the relationships that actually exist in the world